Behavioral analysis of cybercrime: Paving the way for effective policing strategies - Gargi Sarkar; Sandeep K. Shukla (Journal of Economic Criminology, 2023)
This comprehensive survey paper offers a panoramic exploration of the dynamic realm of cybercrime policing, encompassing a wide spectrum of intricacies from cybercrime definitions to establishing a robust investigative framework. Navigating through the intricate tapestry of cybercrime, the study meticulously classifies and contextualizes cybercrime taxonomies, typologies, and defining attributes. Emphasizing the importance of a holistic understanding, the research dissects the stages of cybercriminal activities, shedding light on the multifaceted strategies employed in executing cybercrimes. By deconstructing the entire cybercrime lifecycle, this paper enhances the granularity of comprehending cyber incidents, consequently facilitating more effective investigative preparedness. An essential focal point of this investigation is the indispensable role of digital artifacts in the cybercrime landscape. The study underscores their pivotal significance in catalyzing cybercrime investigations and shaping the trajectory of law enforcement efforts. Additionally, the study probes the repercussions of cybercrime on victims, dissecting the complex interplay between public perception of policing and law enforcement’s perspective on victims. Amid the intricate challenges faced by cybercrime policing, the research uncovers diverse investigation approaches and underscores the criticality of well-defined digital investigation procedures. Moreover, the study delves into the symbiotic collaboration between public and private sectors, highlighting the joint efforts of private entities and law enforcement agencies in combatting cybercrimes. A cornerstone of this survey is the evaluative scrutiny of existing investigative models, culminating in the proposition of a robust and comprehensive cybercrime investigation framework. Rooted in meticulous research methodologies, this endeavor contributes a valuable resource poised to inform and guide future research in the ever-evolving field of cybercrime policing. As the digital landscape continues to evolve, this survey paper equips law enforcement with essential insights to navigate the complexities of cybercrime and safeguard digital realms with utmost efficacy.